Visible-Light-Mediated Germanylation of Aryl Fluorides: Synthetic and Mechanistic Insights - Magné, Valentin; Bellanger, Corentin; Hussein, Aqeel A.; Saffon-Merceron, Nathalie; Lakhdar, Sami (Synthesis, 2023)
We describe herein a metal-free synthesis of aryltriphenylgermanes from the reaction of triphenylgermane with fluoro(hetero)arenes in the presence of a base under blue light irradiation. The reaction proceeds under mild conditions and tolerates a few functionalities. The scope and limitations of this unprecedented approach are analyzed based on preliminary mechanistic studies.
Keywords: germanylation; photochemistry; mechanism; DFT calculations